AN EXPLORATORY STUDY ON THE SIGNIFICANCE OF INTANGIBLE ASSET IN MUSHARAKAH-BASED FRANCHISING - Munirah Kasim,; Nasri Naiimi,; Mohamad Akram Laldin, (Journal of Islamic, Social, Economics and Development, 2023)
This paper is an exploratory study aims to offer the franchise industry with the Islamic based franchise system through musharakah. The paper tries to present the feasibility of intangible asset to be considered as capital in forming musharakah-based franchise. Franchisor may contribute capital in the form of intangible asset, whereas franchisee provide financial resources as capital. Qualitative approach was used through in-depth interview consisting of five experts in muamalat and franchise industry, and six franchisors from the industry. The paper reveals that intangible assets such as trade mark, brand, patent, skills, and experience are assets which has financial value, and they are acceptable to serve as capital in the musharakah-based franchise. This finding spark insight ideas on significance of intangible capital in the franchise industry where it creates win-win situation between franchisors and franchisee to grow their business.